Human Papilloma Virus Prevalence in a Multiethnic Screening Population. Issue 3 (8th January 2013) - Chen, Kang Mei; Stephen, Josena K.; Ghanem, Tamer; Stachler, Robert; Gardner, Glendon; Jones, Lamont; Schweitzer, Vanessa P.; Hall, Francis; Divine, George; Worsham, Maria J.
Abstract : Objective: The goal was to determine the prevalence of high‐risk HPV16 using saliva in a screening population in Detroit, Michigan. Materials and Methods: Real‐time quantitative polymerase chain reaction was applied to detect HPV16 in saliva DNA from 349 screening subjects without head and neck cancer (HNC), 156 with HNC, and 19 controls. Cut points for human papilloma virus (HPV) positivity were >0 and >0.001 copy/cell. Proportions were compared between groups using exact χ 2 or Fisher exact tests ( P <. 05). Results: At a cut point >0, each group had an overall HPV prevalence of more than 5%, with a higher prevalence of 30.8% in the HNC patient group. At a cut point >0.001, the prevalence was lower: 0% in the control, 1.2% in the screening, and 16.7% in the HNC group. In the latter, for both cut points, HPV prevalence was different across sites (<0.001) and significantly higher in the oropharynx than larynx or site as other after Hochberg's adjustment. At >0, women in the screening group had a higher prevalence of HPV than did men ( P =. 010), and at >0.001, the prevalence was higher for men in the HNC group than for women ( P =. 035). In the screening group, at >0, only African Americans had a higher prevalence than Caucasian Americans ( P =. 025). Conclusions: In the screening group, a 6.9% and 1.2% screening rate was noted at cut points >0 and >0.001, respectively. The results provide data to inform public health considerations of the feasibility of saliva as a screening tool in at‐risk populations with the long‐term goal of prophylactic vaccination against oral HPV.